ETNOTEKNOLOGI BERBURU DAYAK KUBIN DI DESA MANGGALA KECAMATAN PINOH SELATAN KABUPATEN MELAWI - Firdaus, Ari; Kartikawati, Siti Masitoh; Roslinda, Emi (JURNAL HUTAN LESTARI, 2019)
Traditional hunting is hunting using traditional tools, such as traps, chopsticks, spears, arrows, root and barracks to hunt fish in the river. Hunting equipment used is simple, the material is easily obtained in the surrounding environment and can be assembled and made by yourself. and crossbow. Manggala Village is a village in Melawi Regency where the people are still doing hunting activities, especially the Dayak Kubin tribe, even though Manggala Village has become the center of South Pinoh Sub-district and the conditions are already relatively advanced. This study aims to record the species of animals that are targeted by the Dayak Kubin community in Manggala village, Pinoh Subdistrict, South Melawi District, and examine the hunting techniques and tools used for hunting Dayak Kubin. This study uses a survey method, the determination of respondent with purposive sampling. Number of animal species utilized and targeted by Dayak Kubin people in Manggala Village, Pinoh Selatan District, Melawi Regency, as many as 12 species of 12 families, 2 types of animals, 1 family consisting of 1 species. Dayak Kubin hunting activities carried out by groups and individuals. Tools used in hunting activities are spears, snares, trawl, traps and fishing rods. Hunting techniques carried out by the Dayak Kubin people still use traditional methods such as the materials used are still derived from forest plants such as leaves and bark made concoctions, perform rituals before hunting.Keywords:Dayak Cubic Tribe, Etnotecnology, Hunting Technique